Analysis of Creative Thinking Skills Through the Application of a Scientific Approach Based on Academic Ability Disparity - Neni Hasnunidah; Dian Aulya; Arwin Surbakti (Magister Pendidikan Biologi, Universitas Negeri Medan, 2022)
Creative thinking skills are crucial for students in facing challenges and obstacles in the future. This study aims to analyze the creative thinking skills of students based on differences in academic abilities. This type of research is comparative with the ex post facto research design. The sample selection technique using purposive sampling obtained a sample of 114 students. The results showed that there were significant differences in creative thinking skills (p <0.05) between students with higher, moderate, and lower academic abilities. Creative thinking skills of students with higher academical abilities were significantly different (p <0.05) from students with lower academic, but not significant (p> 0.05) from students with moderate academic. Creative thinking skills of students with moderate academic abilities were not significantly different (p> 0.05) with students with lower academic. The average value of creative thinking skills in each group is low because students experience difficulties in empowering creative thinking skills. The benefit of this research is to find out the creative thinking skills of students so that they can be used as a reference in evaluating learning.